Синтез та електрофізичні властивості гетероструктур CuS/CdS та Ag2S/CdS - Prokopenko, S. L.; Gunja, G. M.; Makhno, S. N.; Gorbyk, P. P. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2013)
The semiconductor heterostructures CuS/CdS and Ag2S/CdS based on CdS nanowires where synthesized and investigated in order to assess heir electrophysical properties. The temperature and frequency dependences of the electrical conductivity of fibrous heterostructures are revealed. Was shown that conductivity of the CuS/CdS nanowires heterostructure compared with initial CdS increases in 5 orders of magnitude when the degree of substitution of Cd ions by Cu ions is 85%; and about 4 whereas the 15% of substitution is achieved.